Regional Elastic Properties of the Achilles Tendon Is Heterogeneously Influenced by Individual Muscle of the Gastrocnemius - Jiping Zhou; Jiafeng Yu; Chunlong Liu; Chunzhi Tang; Zhijie Zhang (Applied Bionics and Biomechanics)
Background. Anatomical studies and the mechanical property studies showed that there is a strong correlation between Achilles tendon (AT) elasticity and individual gastrocnemius muscle (the medial head of gastrocnemius (MG) and the lateral head of gastrocnemius (LG)) elasticity. Limited ankle dorsiflexion range of motion has been correlated with decreased flexibility of the MG/LG/AT complex. However, no studies have been conducted to examine the exact correlation between the Achilles tendon and the individual muscle of the gastrocnemius. Purposes. The purposes of the present study were (1) to evaluate intra- and interoperator reliabilities of elastic property measurements in the gastrocnemius muscle-Achilles tendon complex by using the shear wave elastography (SWE) and (2) to examine the correlation between the regional elastic properties of the AT and the individual muscle of the gastrocnemius. Methods. Twenty healthy subjects (mean age: 22.50 (3.02) years) were recruited in this study. The elastic properties of the AT and the individual muscle of the gastrocnemius were quantified using the SWE. Findings. The SWE has comparatively high reliability in quantifying the elastic properties of the muscle-tendon range from good to excellent. The intraoperator ICC of the gastrocnemius muscle-Achilles tendon complex was 0.77 to 0.95, while the interoperator ICC was 0.76 to 0.94. The minimal detectable change (MDC) of the muscle was 1.72 kPa, while the AT was 32.90 kPa. A significant correlation was found between the elastic modulus of AT and the elastic modulus of the MG (r=0.668 and p=0.001 at the relaxing position and r=0.481 and p=0.032 at the neutral position). Conclusions. The SWE has the potential to assess localized changes in muscle-tendon elastic properties, provide more intuitive relations between elastic properties of the muscle tendon and function, and evaluate the therapeutic effect of the muscle tendon. A significant correlation between the AT and the MG was found, and it may provide a new treatment idea (targeted to the tight muscle heads) for the clinical setting to treat subjects with AT disorders.